ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM BPD BERDASARKAN KRITERIA BENJAMIN GRAHAM - Widarto, Farah Ashila Oktavianda; Maski, Ghozali (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research aims to analyze the effect of Earning per Share (EPS), Price Earning Ratio (PER), Dividend Yield (DY), Price to Book Value (PBV), and Current Ratio (CR) on the stock prices of Regional Development Bank based on the criteria of Benjamin Graham. The type of research used is quantitative research. The population in this study is the Regional Development Bank conducted in the third quarter of 2013 to the second quarter of 2023. This study uses secondary data sources with sample selection using purposive sampling method. The data analysis method uses panel data regression analysis. The results of this study indicate that the variables Earning per Share (EPS), Price Earning Ratio (PER), Dividend Yield (DY), Price to Book Value (PBV), and Current Ratio (CR) simultaneously have a significant influence on the stock prices variable. While partially, Price Earning Ratio (PER) and Dividend Yield (DY) variables have a negative and significant influence on stock prices. Price to Book Value (PBV) and Current Ratio (CR) variables have a positive and significant influence on stock prices. Meanwhile, Earning per Share (EPS) variable has a positive and insignificant effect on stock prices.